Enhanced mechanical properties and wear resistance of 2024Al alloy with CeO2 addition. (December 2019) - Lv, Zheng; Liang, Qiushi; Mao, Changhui; Yang, Zhimin; Yang, Jian; Dai, He
Abstract: In this work, a study of the mechanical properties and wear resistance of CeO2 reinforced 2024Al matrix composites have been performed using servohydraulic universal testing machine and ball-on-disk wear system. The composites were fabricated through powder sintering and hot extrusion followed by T4 heat treatment. Matrix of pure 2024Al was used to which different mass fractions (0.2%, 0.5%, 1.5%, 2.5% and 4.0%) of CeO2 were added. Tensile tests were performed at room temperature and velocity of 2.0 mm/min. As the CeO2 content increased, mechanical properties were firstly increased and then decreased. The UTS, YS and elongation reached maximum values at 0.5 mass.% CeO2 addition, which were increased by 11.6%, 13.3% and 20.7% as compared to those of pure 2024Al alloy, respectively. While, wear tests were carried out under loads of 5-20 N with sliding velocity of 0.05 m/s for 60 min. For 0.5 mass.% CeO2 /2024Al, the decrements in volume loss and average COF and maximum COF under load of 10 N were 48.0% and 35.3% and 8.1% respectively as compared with pure 2024Al, and the decrements in volume loss and average COF and maximum COF under load of 20 N were 34.0% and 2.3% and 8.9% respectively as compared with pure 2024Al. Therefore, both mechanical properties and wear resistance of 2024Al alloy were markedly enhanced through trace CeO2 addition.